2017
DOI: 10.1007/s10549-017-4418-y
|View full text |Cite
|
Sign up to set email alerts
|

FOXA1 hypermethylation: link between parity and ER-negative breast cancer in African American women?

Abstract: Background Reproductive factors, particularly parity, have differential effects on breast cancer risk according to estrogen receptor (ER) status, especially among African American (AA) women. One mechanism could be through DNA methylation, leading to altered expression levels of genes important in cell fate decisions. Methods Using the Illumina 450K BeadChip, we compared DNA methylation levels in paraffin-archived tumor samples from 383 AA and 350 European American (EA) women in the Women’s Circle of Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 32 publications
1
33
0
Order By: Relevance
“…In addition, FOXA1 regulatory regions are highly susceptible for DNA methylation and transcriptional repression, particularly in the context of BRCA1 deficiency (49). Furthermore, ER À tumors in AA women show elevated FOXA1 DNA methylation compared with ER À tumors of EA women (30). Recent studies have also demonstrated racial differences in plasma levels of cytokines with CCL2, CCL11, IL4, and IL10 being higher in EA women, and IL1RA and IFNa2 being higher in AA women (50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, FOXA1 regulatory regions are highly susceptible for DNA methylation and transcriptional repression, particularly in the context of BRCA1 deficiency (49). Furthermore, ER À tumors in AA women show elevated FOXA1 DNA methylation compared with ER À tumors of EA women (30). Recent studies have also demonstrated racial differences in plasma levels of cytokines with CCL2, CCL11, IL4, and IL10 being higher in EA women, and IL1RA and IFNa2 being higher in AA women (50).…”
Section: Discussionmentioning
confidence: 99%
“…While higher expression of FOXA1 in the primary tumor is associated with better outcome, its overexpression in metastatic and/or anti-estrogen-resistant tumors is associated with rewiring of ERa signaling and poor outcome (26)(27)(28)(29). In addition, it is suggested that FOXA1 gene is preferentially methylated in tumors of AA women (30). Because of its relative importance in breast cancer, we assessed our TMA for FOXA1 expression.…”
Section: Foxa1 Expression Is Lower In Nats Of Only Aa Womenmentioning
confidence: 99%
“…Among the 58 breast tumors included in the miRNA-seq, RNA-seq was performed on 50 tumors, as described previously (22). Briefly, a 1 μg's aliquot of RNA quantified by Quant-iT RiboGreen RNA assay Kit (Invitrogen #R11490) was used for library preparation using TruSeq(r) Stranded Total RNA LT with Ribo-Zero TM Gold (Illumina #RS1222301).…”
Section: Rna-seq and Data Processingmentioning
confidence: 99%
“…Speci c methylation patterns have been associated with high tumor grade and ER negativity of breast cancer (4,(7)(8)(9). In our own studies and others, analyses restricted to CpG dinucleotides (CpGs) within and nearby PCGs, show differences in DNA methylation patterns in tumors by ER status and between AA and EA women (10)(11)(12)(13). These results suggest that aggressive breast cancer subtypes may be related to altered gene methylation, and that methylation patterns may differ by ancestry.…”
Section: Introductionmentioning
confidence: 52%